LITERASI INVESTASI DAN FINANCIAL SELF EFFICACY TERHADAP KEPUTUSAN INVESTASI KELOMPOK STUDI PASAR MODAL SE KABUPATEN JOMBANG - Lik Anah; Choirun Nisful Laili; Lilis Sugi Rahayu Ningsih (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Abstract This study aimed to determine the effect of Capital Market Investment Literacy and Financial Self Efficacy on the Investment Decisions of the Capital Market Study Group Investment Galleries throughout Jombang Regency Investing in the capital market that can be made by all people, especially young people. The Indonesia Stock Exchange also continues to improve capital market education among young people by opening investment galleries in universities with various educational activities and services for opening investment accounts in the capital market. This research using quantitative descriptive with purposive sampling technique in the capital market study group in Jombang. Analysis data using multiple linear regression, with the t-test, F test, and the coefficient of determination. The results shows that capital market investment literacy has a significant influence on investment decisions. Financial self-efficacy has a significant effect on investment decisions Capital market investment literacy and financial self-efficacy have a simultaneous effect on investment decisions in the capital market study group investment galleries throughout Jombang Regency. Keywords: Literacy, Self Efficacy, Decisions, Investment